2017
DOI: 10.1177/2325967117714998
|View full text |Cite
|
Sign up to set email alerts
|

Distal Musculotendinous T Junction Injuries of the Biceps Femoris: An MRI Case Review

Abstract: Background:Injury to the distal musculotendinous T junction (DMTJ) of the biceps femoris is a distinct clinical entity that behaves differently from other hamstring injuries due to its complex, multicomponent anatomy and dual innervation. Injury in this region demonstrates a particularly high rate of recurrence, even with prolonged rehabilitation times.Purpose:To describe the anatomy of the DMTJ of the biceps femoris and analyze the injury patterns seen on magnetic resonance imaging (MRI) to aid prognosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 41 publications
2
63
1
Order By: Relevance
“…Distally, the biceps femoris is a complex structure, arising from 2 separately innervated muscles (long head of biceps femoris and short head of biceps femoris), emerging from different origins proximally with dissimilar force vectors. 16 , 31 The short head component, originating from the linea aspera on the posterior aspect of the femoral diaphysis, converges and coalesces with the tendon of the long head of the biceps femoris (originating from the ischial tuberosity) in the posterolateral aspect of the distal half of the thigh. 6 , 31 In their study of 30 cadaveric knees, Terry and LaPrade 31 provided detailed anatomic descriptions of the tendinous insertions of the distal biceps femoris.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distally, the biceps femoris is a complex structure, arising from 2 separately innervated muscles (long head of biceps femoris and short head of biceps femoris), emerging from different origins proximally with dissimilar force vectors. 16 , 31 The short head component, originating from the linea aspera on the posterior aspect of the femoral diaphysis, converges and coalesces with the tendon of the long head of the biceps femoris (originating from the ischial tuberosity) in the posterolateral aspect of the distal half of the thigh. 6 , 31 In their study of 30 cadaveric knees, Terry and LaPrade 31 provided detailed anatomic descriptions of the tendinous insertions of the distal biceps femoris.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the tendinous component of the short head’s direct arm inserts lateral to the fibular styloid and medial to the FCL, with the anterior arm inserting medial to the FCL and converging anteriorly with the anterior tibiofibular ligament, while also continuing laterally onto the tibia, 1 cm posterior to Gerdy’s tubercle. In a review of 106 MRIs from patients sustaining acute, indirect injuries to the distal biceps femoris, Entwisle et al 16 found that the majority of injuries were isolated to the long head of the biceps (51%, n = 54/106) and attributed this to the fact that the long head crosses both the hip and knee joint, while isolated injuries to the short head component were rare (6.6%, n = 7/106).…”
Section: Discussionmentioning
confidence: 99%
“…Injuries to the distal MTJ of the biceps femoris present a special clinical challenge due to its complex anatomic structure and dual innervation to the short and long head of the muscle. 11 As the long and short head of the biceps femoris merge together at the distal MTJ, they form a T-shaped aponeurosis. Injuries occurring in this region are demanding to treat; despite long rehabilitation times, the recurrence rates are the highest among skeletal muscle injuries reported to date, as more than 50% of patients sustain reinjury.…”
Section: Analysis Of Typical Injuries According To the Model Hamstrinmentioning
confidence: 99%
“…Injuries occurring in this region are demanding to treat; despite long rehabilitation times, the recurrence rates are the highest among skeletal muscle injuries reported to date, as more than 50% of patients sustain reinjury. 11 Because the maturation of scar tissue is a slow process, it has been recommended that MRI be used to determine proper scar maturation before RTP can be considered. 11 We can observe all 3 types of histoarchitectonic involvement in the common hamstring tendon in daily clinical practice: direct tendon involvement with gap ( Figure 6A), purely myotendinous injury without gap ( Figure 6B), and muscle injury produced by traction of the common tendon but without direct contact with it ( Figure 6C).…”
Section: Analysis Of Typical Injuries According To the Model Hamstrinmentioning
confidence: 99%
See 1 more Smart Citation